The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/met9020174
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Modelling on Nanoscale Growth of Magnesia Inclusion in Fe-O-Mg Melt

Abstract: Nano-magnesia is the intermediate product during the growth of magnesia inclusion in Mg-deoxidized steel. Understanding the thermodynamics on nano-magnesia is important to explore the relationship between magnesia product size and deoxidation reaction in molten steel. In this work, a thermodynamic modeling is developed to study the Mg-deoxidation reaction between nano-magnesia inclusions and liquid iron. The thermodynamic results based on the first principle method show that the Gibbs free energy change for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In addition, Wang et al [32][33][34] suggested that the thermodynamic of Al-deoxidation in liquid iron is closely related with the size of alumina. Xiao et al [35][36][37] reported that the deoxidation thermodynamics of metal in liquid iron have depended on the structures and properties of reaction products. Hence, it can be concluded that there is a close relationship between the thermodynamics of Al-deoxidaiton reaction in liquid iron and metastable phase, such nano-Al 2 O 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Wang et al [32][33][34] suggested that the thermodynamic of Al-deoxidation in liquid iron is closely related with the size of alumina. Xiao et al [35][36][37] reported that the deoxidation thermodynamics of metal in liquid iron have depended on the structures and properties of reaction products. Hence, it can be concluded that there is a close relationship between the thermodynamics of Al-deoxidaiton reaction in liquid iron and metastable phase, such nano-Al 2 O 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The initial structures of (Al 2 O 3 ) 2 cluster and α-Al 2 O 3 crystal were selected from the previous work 33 . The Gibbs free energy of (Al 2 O 3 ) 2 cluster and α-Al 2 O 3 crystal were calculated by the equations [33][34][35][36][37] where E is the total energy of alumina cluster or crystal at 0 K; H and S are the enthalpy and entropy of alumina cluster or crystal, respectively. The H and S were obtained by the analysis of atomic harmonic vibrational frequency of alumina cluster or crystal, which are the functions of temperature T. The calculation details of the relationship among the atomic harmonic vibrational frequency, the thermodynamic properties and temperature can be found in our previous study [33][34][35][36][37] .…”
Section: Theoretical Calculation Thermodynamic Modeling Of Nano-al 2 mentioning
confidence: 99%
See 1 more Smart Citation